2021
DOI: 10.1002/pri.1923
|View full text |Cite
|
Sign up to set email alerts
|

Dizziness and physical health are associated with pain in dizzy patients—A cross‐sectional study

Abstract: Background and Purpose: Associations between dizziness, health-related quality of life, and musculoskeletal pain have not been systematically explored in patients with vestibular disorders. Such knowledge may be important for choice of treatments.The study objectives were to examine the extent and localization of musculoskeletal pain and explore whether pain was associated with dizziness and health-related quality of life. Methods: The cross-sectional study investigated anonymized data from an earlier survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…Association between pain intensity as the dependent variable, and dizziness symptoms, dizziness-related handicap, or dizziness catastrophizing thoughts as independent variables, examined with linear regression analysis.The high prevalence of pain reported in our study is in line with other studies on patients with dizziness(Gustavsen et al, 2021;Malmström et al, 2021;Moen et al, 2022). Despite that estimates of pain prevalence may vary between studies due to differences in methodology, de nitions, and context, the prevalence in the current study was substantially higher than in the general population in Norway (94.5% versus 25%) (Kinge, Knudsen, Skirbekk, & Vollset, 2015;Rustøen et al, 2004).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Association between pain intensity as the dependent variable, and dizziness symptoms, dizziness-related handicap, or dizziness catastrophizing thoughts as independent variables, examined with linear regression analysis.The high prevalence of pain reported in our study is in line with other studies on patients with dizziness(Gustavsen et al, 2021;Malmström et al, 2021;Moen et al, 2022). Despite that estimates of pain prevalence may vary between studies due to differences in methodology, de nitions, and context, the prevalence in the current study was substantially higher than in the general population in Norway (94.5% versus 25%) (Kinge, Knudsen, Skirbekk, & Vollset, 2015;Rustøen et al, 2004).…”
supporting
confidence: 89%
“…However, neck pain is also found to be part of a widespread pain pattern in the general population (Natvig, Ihlebaek, Grotle, Brage, & Bruusgaard, 2010), and this could probably apply to dizziness populations as well. A recent systematic review found that pain in other body parts is also evident in patients with dizziness (Moen et al, 2022), and dizziness is further found to be associated with local as well as widespread pain (Gustavsen et al, 2021). It is possible to speculate that both dizziness and pain could have a mutual preserving effect on each other as both symptoms could result in a more rigid movement pattern, leading to increased muscular tension and reduced recovery from dizziness (Coelho Júnior et al, 2010;Wilhelmsen & Kvåle, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their results have clear points of contact with the present study in that the neck had significance for the health status and that there was a covariation between neck and dizziness. Gustavsen et al 42 studied associations between musculoskeletal pain, dizziness and health-related quality of life, with pain as the dependent variable. They found that musculoskeletal pain was associated with increasing dizziness, and the combination of neck pain and dizziness was proposed as a possible trigger of persistent postural-perceptual dizziness (PPPD).…”
Section: Discussionmentioning
confidence: 99%
“…Dizziness sometimes accompanies neck pain or related disorders 42 but pain in the upper neck can nonetheless occur without comorbidity of dizziness. Therefore, the assessment of patients with this type of symptoms would most likely benefit from screening with pain drawing along with balance measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation